2012
DOI: 10.1080/09583157.2011.648167
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation ofDiachasmimorpha longicaudata(Hymenoptera: Braconidae) as a mortality factor ofCeratitis capitata(Diptera: Tephritidae) infestingCitrusspecies under laboratory and field-cage conditions

Abstract: 2012): Evaluation of Diachasmimorpha longicaudata (Hymenoptera: Braconidae) as a mortality factor of Ceratitis capitata (Diptera: Tephritidae) infesting Citrus species under laboratory and field-cage conditions, Biocontrol Science and Technology, 22:2, 187-202 To link to this article: http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 45 publications
1
19
1
Order By: Relevance
“…Several studies have demonstrated that D. longicaudata tends to superparasitize host larvae strongly not only under laboratory conditions (Montoya et al, 2011;González et al, 2010) but also under natural field conditions (Montoya et al, 2013). This may increase efficacy of the female parasitoid on the host (Ovruski et al, 2012). In addition, Montoya et al (2000b) Interestingly, a certain level of association between temperature and parasitoid effectiveness was detected.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies have demonstrated that D. longicaudata tends to superparasitize host larvae strongly not only under laboratory conditions (Montoya et al, 2011;González et al, 2010) but also under natural field conditions (Montoya et al, 2013). This may increase efficacy of the female parasitoid on the host (Ovruski et al, 2012). In addition, Montoya et al (2000b) Interestingly, a certain level of association between temperature and parasitoid effectiveness was detected.…”
Section: Discussionmentioning
confidence: 97%
“…Given this fact and due to several other reasons, D. longicaudata was considered to be suitable for augmentative releases in San Juan. The most relevant arguments to do so are the adaptability of D. longicaudata to the different environments into which it has been introduced (Ovruski et al, 2000), the development of efficient techniques for massrearing in Hawaii (Vargas et al, 2012) and México (Montoya et al, 2007), its capacity for successful development on the C. capitata larvae infesting fruit under field conditions (Ovruski et al, 2012), and its host-finding ability at different host-densities on a wide variety of fruit species and at canopy and ground levels (García-Medel et al, 2007). Therefore, D. longicaudata is being mass-reared at the BioPlanta San Juan facilities with the aim of using it for mass-releasing in organic growing areas and cultivated suburban locations in order to achieve suppression or selected eradication of medfly populations (Suárez et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the parasitism percentage and fertility were higher in peach, cementine and orange than on apple. This was the same for Segura et al (2016) and in contradiction with the results obtained by Leyva et al (1991) and Ovruski et al (2012) longicaudata, at least not an association that completely explains the preference for host habitats.…”
Section: Host Fruit Influence On Parasitism Activity: Semi-field Trialscontrasting
confidence: 56%
“…Moreover, we have determined a link between host fruit preference parasitism rate and fertility in a similar way as determined by Segura et al (2016) but of opposite sign to Leyva et al (1991) and Ovruski et al (2012). With our focal point control trials, we obtained 30-63% of medfly population reduction (Table 3.6), that corresponds to a higher parasitism rate when compared to laboratory conditions either obtained by us or by other researchers.…”
Section: Biotic and Abiotic Factors Affecting Parasitic Activity Of Dmentioning
confidence: 55%
“…This tephritid species is widely distributed throughout Argentina, and severely limit the export of fresh fruit as a result of quarantine restrictions in countries free of this pest [1]. In Argentina's northern Citrus-producing regions, C. capitata is actively multiplying in large exotic host fruits, such as Citrus paradisi Macfadyen (grapefruit), Citrus aurantium L. (sour orange) and Citrus sinensis L. (Osbeck) (sweet orange) (Rutaceae), all originated in Southeast Asia [2]. These Citrus species are commonly found in abandoned crop fields or in disturbed wild vegetation areas [3].…”
Section: Introductionmentioning
confidence: 99%